2022
DOI: 10.1002/ski2.151
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and developing a paediatric psychodermatology service and our experience of a new paediatric psychodermatology clinic during the Covid 19 pandemic

Abstract: Children and young people (CYP) with skin and hair conditions are at an increased risk of mental health problems and vice versa. Current child and adolescent mental health services are already stretched and in our experience, this unique combination of symptoms and signs requires a multi‐disciplinary approach. We report our experience of establishing a paediatric psychodermatology clinic where, at each appointment, CYP are seen by a consultant dermatologist and a clinical psychologist initially jointly and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…56 Anecdotal evidence may also support the implantation of psycho-dermatology clinics involving both dermatologists and clinical psychologists in the management of childhood eczema and improving HRQoL for families. 57 In this style of clinic, patients and their caregivers can see both a consultant dermatologist, for medical treatment and a clinical psychologist who manages psychological concerns through strategies such as habit reversal for itch. Mindfulness therapy for parents has also been shown to improve both disease severity and QoL in a very small case series parameters in small case series.…”
Section: Resultsmentioning
confidence: 99%
“…56 Anecdotal evidence may also support the implantation of psycho-dermatology clinics involving both dermatologists and clinical psychologists in the management of childhood eczema and improving HRQoL for families. 57 In this style of clinic, patients and their caregivers can see both a consultant dermatologist, for medical treatment and a clinical psychologist who manages psychological concerns through strategies such as habit reversal for itch. Mindfulness therapy for parents has also been shown to improve both disease severity and QoL in a very small case series parameters in small case series.…”
Section: Resultsmentioning
confidence: 99%
“…4 For example, Sears et al reported their experience of establishing a pediatric psychodermatologic clinic composed of a consultant dermatologist and a clinical psychologist for establishment of a collaborative treatment plan during the COVID-19 pandemic, and patients and their families found this clinic to be helpful and effective. 52 This review is focused on pharmacological interventions, which limits the ability to compare non-pharmacological approaches to PPDs such as cognitive behavioral therapy and stress reduction techniques (e.g., meditation), and even some physical modality has shown benefits. For example, Christensen et al reported cases of using microneedling a novel treatment option for patients with trichotillomania.…”
Section: Discussionmentioning
confidence: 99%
“… 4 For example, Sears et al reported their experience of establishing a pediatric psychodermatologic clinic composed of a consultant dermatologist and a clinical psychologist for establishment of a collaborative treatment plan during the COVID-19 pandemic, and patients and their families found this clinic to be helpful and effective. 52 …”
Section: Discussionmentioning
confidence: 99%
“…In this special edition of Skin Health and Disease we aim to showcase the breadth and depth of psychodermatology research, covering genetic and acquired skin diseases, involving patients across the entire age spectrum suffering from primary skin or psychiatric diagnoses. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Furthermore, we report the potential of medications to trigger autoimmune blistering disease in patients with neuropsychological disorders. 6 The issue also includes robust prospective epidemiological data from national registries examining associations between mental health and psoriatic arthritis in patients with psoriasis as well as charting the development of psychodermatology clinics and liaison services 7 and the establishment of patient reported outcomes measures for body image in dermatology is detailed.…”
mentioning
confidence: 90%
“…In this special edition of Skin Health and Disease we aim to showcase the breadth and depth of psychodermatology research, covering genetic and acquired skin diseases, involving patients across the entire age spectrum suffering from primary skin or psychiatric diagnoses 6–19 . Furthermore, we report the potential of medications to trigger autoimmune blistering disease in patients with neuropsychological disorders 6 .…”
mentioning
confidence: 99%